Psychosocial factors associated with psychological distress and functional difficulties in recently transitioned and current serving regular Australian Defence Force members. (April 2020) - Hansen, Craig; McFarlane, Alexander; Iannos, Marie; Sadler, Nicole; Benassi, Helen; Lawrence-Wood, Ellie; Hodson, Stephanie; Searle, Amelia; Van Hooff, Miranda
Highlights: Those who were highly distressed/impaired were 18 times more likely to report insomnia (than those with low distress/impairment). Those who were highly distressed/impaired were seven times more likely to report low resilience (than those with low distress/impairment). Those who were highly distressed/impaired were seven times more likely to have more than 11 self-reported physical health symptoms (than those with low distress/impairment). The associations between psychological distress/impairment and insomnia and self-reported physical health symptoms were stronger among the transitioned cohort than the regular 2015 ADF. Abstract: The transition period from military-to-civilian life can be one of the most significant and stressful periods in the military life cycle. We explore the psychosocial factors associated with psychological distress and functional impairment among those who recently transitioned from the Australian Defence Force (ADF) and those currently serving in 2015. Using data from the Transition and Wellbeing Research Programme, multinomial logistic regression models were used to analyze the associations between a combined measure of psychological distress and functional impairment (K10/SDS) with various psychosocial, lifestyle, and physical health factors. There were 10, 210 in the final analytic cohort (Transitioned=3, 254; Regular 2015 ADF=6, 956). Overall, the odds of belonging to the highly distressed/impaired group were greatest among those with insomnia (Odds Ratio 18.53), low resilience (OR 7.67), physical health symptoms (OR 7.16), and alcohol risk (OR 4.67). Other factors included pain (OR 3.36), financial issues (OR 2.38), and social strain (OR 1.98). The associations with insomnia and physical health symptoms were stronger among the Transitioned compared to the Regular 2015 ADF. Results of this research highlights the importance of taking a multi-dimensional perspective of symptoms in military populations, particularly in those recently transitioned from permanent service, as predictors of future risk of disorder.